حوكمة الصفقات العمومية كآلية لمكافحة الفساد في الجزائر - خيرة, شريط (جامعة الوادي.University eloued, 2021)
الصفقات العمومية اكثر مجال عرضة للفساد وذلك لأنها من اهم الوسائل التي تعتمد عليها الدولة في دفع عجلة التنمية وتطوير الاقتصاد الوطني، وهو ما دفع المشرع الجزائري الى حوكمتها عبر جميع المراحل من الابرام الى التنفيذ، كما عزز من المبادئ التي تحكم ابرامها بتكريس المساواة لحرية الوصول الى الطلب العمومي، وارساء الشفافية في الاجراءات من خلال ادراجها في نصوص واحكام قانونية في قانون الصفقات العمومية، اضافة الى فرض مبادئ الحوكمة على اليات الرقابة المختلفة سوى على الرقابة الادارية او المالية . فالحوكمة تهدف الى تنفيذ الصفقة في وقتها المحدد وبالشروط المحددة كما انها تهدف الى الحفاظ على حسن سير المنطق العام وترشيد المال والحفاظ عليه من كل اشكال الفساد.Public procurement is the most vulnerable area to corruption، because it is one of the most important means that the state relies on to advance the wheel of development and the development of the national economy، which prompted the Algerian legislator to govern them through all stages from conclusion to implementation، and also strengthened the principles governing their conclusion by dedicating equality to freedom of access to demand. and establishing transparency in the procedures by including them in legal texts and provisions in the public procurement law، in addition to imposing the principles of governance on the various control mechanisms except for the administrative or financial control. Governance aims to implement the deal on time and on the specified terms. It also aims to maintain the proper functioning of the general logic، rationalize money and preserve it from all forms of corruption.
قانون اداري
Keywords: الصفقات العمومية . الحوكمة. الفساد.